7-3x=6x-56

Simple and best practice solution for 7-3x=6x-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=6x-56 equation:


7-3x=6x-56

We simplify the equation to the form, which is simple to understand
7-3x=6x-56

We move all terms containing x to the left and all other terms to the right.
-3x-6x=-56-7

We simplify left and right side of the equation.
-9x=-63

We divide both sides of the equation by -9 to get x.
x=7

See similar equations:

| 4(4x+1)=4x-7x | | 13/3x-2=4/x | | x^4+5*x^3+9*x^2+8*x+4=0 | | 3-7x+2x=-37 | | 9x-26=30-5x | | 12t^2-5t+6=8 | | ln(p+10)=1 | | 8w+8=16 | | -9y+9=72 | | 0.30x+0.20(60)=0.15(32) | | -5(2x-9)=2(x-6)-11 | | 4x^4+8x^3+16x^2=0 | | 13x+3=29 | | 4w/3=4 | | 96x-624=336 | | -x+4x=8x-x+6 | | ln(6n)=3 | | (3x+3y)2= | | 5-2y=2+4y | | -5+x=-6x-5 | | f(x)=5-x^2/4 | | 0.36-a^2=0 | | 15=3r-3 | | 0.2047244=(1800*(96^3))/((10*10^6)*48*((b*(3.75^3)-(b-.5)*(3.25^3))/12)) | | 5.3x-6.45=7.95-4.3z | | g(-3)=0 | | -6x-3=5/7x-538/7 | | y=-3x+1.5 | | x+0.12x=1488 | | Log(x+1)16=8 | | -4x-3y=15fory | | 6+y=-6y |

Equations solver categories